2020
DOI: 10.1002/adma.202005096
|View full text |Cite
|
Sign up to set email alerts
|

Imaging Cellular Aerobic Glycolysis using Carbon Dots for Early Warning of Tumorigenesis

Abstract: is crucial for developing a better understanding of how tumors develop and progress. In this context, great achievements have been made using fluorescence imaging to detect tumors with high sensitivity and quality. [2-4] The current fluorescence-imaging strategies used to identify tumor cells are based on the conjugation of ligands and targeting of receptors, including peptides, proteins, antibodies, and aptamers. [5,6] However, it is difficult to realize early warning of tumor formation using fluorescence ima… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(38 citation statements)
references
References 19 publications
0
38
0
Order By: Relevance
“…[ 25 ] Carbon dots (CDs), a new type of fluorescent nanomaterial, [ 26,27 ] display unique properties of small size, facile preparation, low cost, good biocompatibility, and excellent optical properties. [ 27–30 ] Therefore, CDs have attracted particular attention in various biomedical applications, [ 29–34 ] including in the field of bone regeneration. [ 35,36 ] The various medications provide abundant raw materials for preparing CDs.…”
Section: Introductionmentioning
confidence: 99%
“…[ 25 ] Carbon dots (CDs), a new type of fluorescent nanomaterial, [ 26,27 ] display unique properties of small size, facile preparation, low cost, good biocompatibility, and excellent optical properties. [ 27–30 ] Therefore, CDs have attracted particular attention in various biomedical applications, [ 29–34 ] including in the field of bone regeneration. [ 35,36 ] The various medications provide abundant raw materials for preparing CDs.…”
Section: Introductionmentioning
confidence: 99%
“…CDs will not damage organisms’ life activity when they enter the organisms because of its good biocompatibility of CDs. As for extracorporeal cell imaging, Li et al [136] . found that CDs were not only limited to clathrin‐mediated endocytosis and active transported into cytosol, but they could also enter cells through free diffusion.…”
Section: Application Of Lc‐cdsmentioning
confidence: 99%
“…The carbon dots were originated from the fragments of singlewalled carbon nanotubes (SWCNTs), which can be refined into graphene quantum dots (GQDs) and carbon quantum dots (CQDs), according to the hybridization and crystallinity of nanomaterials [66,69]. As traditional fluorescent nanoparticles, carbon dots were revalued in recent years since the exceptional chemical properties [17,29,33], including low toxicity, outstanding biocompatibility, and chemical inertness, endowed promising biological applications [27,34,40], such as biosensing, medical diagnosis, bioimaging, and tumor therapy.…”
Section: Carbon Dotsmentioning
confidence: 99%